Biodiversitas Semut di Wilayah Gading Serpong, Tangerang - Alfonsius, Giovani; Lestari, Lo Bunga; Wijaya, Viorenda Thery; Ivan, Fransiskus Xaverius (Surya University, 2016)
Nowadays, ants have become a very interesting research subject due to their roles in environments, including as âecosystems engineersâ and predators. Nonetheless, ant research in Indonesia is still rare, and hence it needs to be encouraged. Here we present the results of our investigation on ant biodiversity in Gading Serpong, Tangerang, which was conducted in the early of 2016.The investigation was done by collecting ants from 20 spots, and followed by the identification of ant species based on their morphological characteristics. Overall, we uncovered that there are 26 ant species from 7 subfamilies in Gading Serpong area. The most abundant species wasForelius mccooki, which has been known for their likeness to dry and hot environment. In addition, the Shannon-Wiener index of 2.72 indicates that the ant biodiversity atGading Serpong area isat moderate level, andthus the pollution level in Gading Serpong area is still of moderate impact.